De NovoSan Luis Valley Syndrome-like der(8) Chromosome With a Concomitant dup(8p22) in a Mexican Girl - Sánchez Casillas, Alma Laura; Rivera, Horacio; Castro Martínez, Anna Gabriela; García Ortiz, José Elías; Córdova Fletes, Carlos; Mendoza Pérez, Paúl (2016)
The rec(8)dup(8q)inv(8)(p23.1q22.1) chromosome associated with San Luis Valley Syndrome (SLVS OMIM 179613) is usually diagnosed in Hispanic patients from the USA Southwest where a founder carrier Spaniard lived around 1800 [1, 2]. This rec(8) has an 8q duplication of 47.90 Mb and an 8p deletion of 11.65 Mb [3, 4]. Excluding two de novo rec(8)dup q chromosomes characterized only by G-bands and included in a recent compilation [5], cytogenomic analyses identified nine comparable de novo der(8)dup q/del p chromosomes with or without a simultaneous 8p gain. We describe a Mexican mestizo girl with a de novo SLVS-like der(8) but with a concomitant 8p22p23.1 duplication